Deep sequencing of small RNAs from 11 tissues of grass carp Ctenopharyngodon idella and discovery of sex‐related microRNAs. Issue 1 (26th December 2018) - Chen, Liangming; Huang, Rong; Zhu, Denghui; Yang, Cheng; He, Libo; Li, Yongming; Liao, Lanjie; Zhu, Zuoyan; Wang, Yaping
Abstract : This research identified 169 known microRNAs (miRNAs), 380 novel miRNAs, and 30, 538 targets in 11 tissues (blood, brain, derma, gill, heart, intestine, kidney, liver, muscle, pronephros, and spleen) from grass carp Ctenopharyngodon idella with high‐throughput sequencing (HTS). Transcripts per million (TPM) expression analysis detected 41 brain‐enriched miRNAs (accounting for 61.19% of all tissue‐enriched miRNAs). Real‐time quantitative PCR (RT‐qPCR) confirmed that 21 of 24 randomly selected tissue‐enriched miRNAs from the TPM analysis were indeed tissue‐enriched ( P < 0.05), suggesting the HTS and TPM analyses were reliable. Nine of the 41 brain‐enriched miRNAs are complementary to members of the double‐sex and mab‐3 related transcription factor family ( dmrt ) involved in sex differentiation. RT‐qPCR revealed that cid‐miR ‐138 was more highly expressed in testis than in ovary ( P < 0.01), while the reverse was true for target gene dmrt4a ( P < 0.01). This opposite expression pattern suggested the direct participation of cid‐miR ‐138– dmrt4a in neuroendocrine mechanisms related to brain‐pituitary networks during sex development. The discovery of miRNAs from 11 C. idella tissues expands the available fish mi R NA database, and enhances our understanding of the role of sex‐related miRNAs in tissue differentiation and maintenance of specific tissue functions in fishes.